2021
DOI: 10.1089/jwh.2020.8879
|View full text |Cite
|
Sign up to set email alerts
|

Change in Health-Related Socioeconomic Risk Factors and Mental Health During the Early Phase of the COVID-19 Pandemic: A National Survey of U.S. Women

Abstract: Background: During a pandemic, women may be especially vulnerable to secondary health problems driven by its social and economic effects. We examined the relationship between changes in health-related socioeconomic risks (HRSRs) and mental health. Materials and Methods: A cross-sectional survey of 3,200 women aged 18-90 years was conducted in April 2020 using a quota-based sample from a national panel (88% cooperation rate). Patterns of change in HRSRs (food insecurity, housing instability, interpersonal viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 54 publications
4
40
0
Order By: Relevance
“…We acknowledge limitations to these findings. Although our dataset closely resembles U.S. population data for women, 28 our findings are limited in generalizability by the use of a panel-based quota sample rather than a probability sample. Our use of an online survey may underestimate food insecurity by excluding a small subset of households with limited internet access—a more prevalent condition among Black and Hispanic households than in White and Asian households.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We acknowledge limitations to these findings. Although our dataset closely resembles U.S. population data for women, 28 our findings are limited in generalizability by the use of a panel-based quota sample rather than a probability sample. Our use of an online survey may underestimate food insecurity by excluding a small subset of households with limited internet access—a more prevalent condition among Black and Hispanic households than in White and Asian households.…”
Section: Discussionmentioning
confidence: 93%
“… 15 , 16 , 59 Our study may be limited by sample size, in particular for analyses with smaller subgroups; the overall study was designed to ensure reasonably precise estimates in subgroups of interest for the primary objectives of the National Women's COVID Health Study (ie, racial/ethnic groups). 28 However, in a post hoc analysis calculating the minimally detectable difference between those with no food restriction and those with both FA and CeD (our smallest comparison group), given that 35% of the sample with no food restrictions were food insecure, we were powered to detect a difference in proportion of food insecurity between groups of 14% (power = 0.80, alpha = 0.05). Similarly, for the subgroup of the sample with CeD (5.4%), we calculate a minimally detectable difference between households with no food restrictions and those with CeD of 12%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 Some studies have reported that COVID-19 mental health effects have been greater for women than men. 5,[15][16][17][18] These, however, have been cross-sectional studies that evaluated proportions of participants above cut-offs on self-report measures without consideration of pre-COVID-19 differences, even though mental health disorders and symptoms are more common among women. [19][20][21][22][23] Evidence from longitudinal cohorts that compare mental health symptoms pre-COVID-19 to during COVID-19 is needed.…”
mentioning
confidence: 99%